2013
DOI: 10.4209/aaqr.2012.07.0173
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Toxicity Evaluation Using Bioindicators and Comet Assay

Abstract: Atmospheric particulate matter (PM) characterizes the atmospheric air quality. PM particles can adsorb and include several toxic air pollutants of urban areas. The current study aimed to develop an experimental procedure to assess the toxicity of the pollutants on PM 10 by means of the comet assay on earthworms directly exposed to PM 10 collecting filters. A particular focus was the amount of polycyclic aromatic hydrocarbons (PAHs) in the filter, in spite of their very low concentration in PM, because of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The application of Comet Assay to earthworms, and consequently the use of such extraordinary prospectors as sentinels for the presence of genotoxicants in soil, started in the nineties of the last century (Singh et al, 1988 ; Verschaeve and Gilles, 1995 ; Salagovic et al, 1996 ), and since then has been extensively revised (Cotelle and Férard, 1999 ; Espinosa-Reyes et al, 2010 ; Liu et al, 2010 ; Atli Şekeroglu et al, 2011 ; Lionetto et al, 2012 ; Andem et al, 2013 ; Vernile et al, 2013 ; Fujita et al, 2014 ; Vasseur and Bonnard, 2014 ; Zhang et al, 2014 ). Several earthworms comparative studies have been performed (Vasseur and Bonnard, 2014 ).…”
Section: Experimental Modelsmentioning
confidence: 99%
“…The application of Comet Assay to earthworms, and consequently the use of such extraordinary prospectors as sentinels for the presence of genotoxicants in soil, started in the nineties of the last century (Singh et al, 1988 ; Verschaeve and Gilles, 1995 ; Salagovic et al, 1996 ), and since then has been extensively revised (Cotelle and Férard, 1999 ; Espinosa-Reyes et al, 2010 ; Liu et al, 2010 ; Atli Şekeroglu et al, 2011 ; Lionetto et al, 2012 ; Andem et al, 2013 ; Vernile et al, 2013 ; Fujita et al, 2014 ; Vasseur and Bonnard, 2014 ; Zhang et al, 2014 ). Several earthworms comparative studies have been performed (Vasseur and Bonnard, 2014 ).…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Resuspended desert dust is an important air pollutant in both local and transboundary levels (Dobrzhinsky et al, 2012). Atmospheric particulate matter (PM) characterizes the atmospheric air quality (Vernile et al, 2013). Urban atmosphere is subject to large inputs of anthropogenic contaminants arising from both stationary (power plants, industries, incinerators, and residential heating) and mobile sources (road traffic) (Pacyna, 1984, Sweet et al, 1993, Sullivan and Woods, 2000, Melaku et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of PM not only affects visibility and causes acidification but also has adverse effects on human health, such as increased respiratory and cardiovascular symptoms and diseases (Harrison and Yin, 2000;Tie et al, 2009;Cheng et al, 2012;Vernile et al, 2013). Moreover, some studies have showed that PM can change the radiation balance, and have important effect on climate change (Bellouin et al, 2005;Tiwari et al, 2012;Tahir et al, 2013).…”
Section: Introductionmentioning
confidence: 99%